PENGARUH FAKTOR-FAKTOR PROFESIONALISME AUDITOR dan ETIKA PROFESI TERHADAP TINGKAT MATERIALITAS DALAM PEMERIKSAAN LAPORAN KEUANGAN - Vinanda Nurul Annisa; Sri Dewi Wahyundaru (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2013)
Audit of financial statements is the most recognized services than other services, also referred to as traditional services. This service is a service that is often used by parties outside the company to assess the company and make decisions relating to the company. In this case the financial statement is the basis for decision making. Financial Lapoaran influenced by the materiality level, because materiality helps the auditor to gather sufficient evidence for the reliability of a financial statement. The title of this research Influence Factors Auditor Professionalism and Professional Ethics On The Level Examination Materiality in Financial Reporting. Type of research is descriptive. The population in this study is the auditor who worked on the Public Accounting Firm ( KAP ) in the city of Semarang. Sampling was done by purposive sampling, and the type of primary data. Analysis techniques in this study using a test testing data quality, validity, and reliability testing. Covers the classical assumption normality test, multicollinearity and heteroscedasticity test and hypothesis testing, regression test, t-test, f and testing the coefficient of determination ( R2 ). Based on the analysis, t-test ( partial ) variable social obligations significance value 0.084 and 0.086 significance value professional ethics do not have a significant effect on the level of materiality, while the variable devotion to the profession with a significance value of 0.017, with a significance value of 0.007 independence, confidence in the profession with values 0.005 significance and relationship with peers significance value of 0.002 has a significant influence on the level of materiality and test results F ( simultaneous ) variable devotion to the profession, social responsibility, self-reliance, confidence in the profession, relationships with colleagues and professional ethics with a value of 0,000 collectively sigifikasi same effect on the level of materiality. Dedication to the profession , self-reliance, confidence in the profession, relationships peers, and professional ethics considerations affect the materiality level so as to produce quality financial statements.